EP804 Prognostic role of second-line platinum-based therapy in recurrent platinum resistant ovarian cancer patients – data from real-world clinical practice in poland. (1st November 2019) - Bodnar, L; Knapp, P; Sznurkowski, J; Mądry, R; Gąsowska-Bodnar, A; Blecharz, P; Sikorska, M; Timorek, A; Ptak-Chmielewska, A; Jach, R; ,
Abstract : Introduction/Background: Strategy of treatment in patients with recurrent ovarian cancer (OC) dependents on platinum-free interval (PFI). We aimed to compare survival in 'platinum resistant' OC patients who received platinum-based or non-platinum chemotherapy at first relapse in real world practice based. Methodology: Data of OC patients treated with primary debulking surgery and standard chemotherapy (paclitaxel/platinum analogs) between January 1, 2011 and December 31, 2011 were extracted from Polish National Health Fund Database. Further overall survival (OS) was compared between patients who received any type of chemotherapy up to 6 months PFI. Results: 17% (227/1369) patients classified as 'platinum-resistant' by the 6-month threshold of PFI and 29% (66/227) of those group, were treated with Pt-based chemotherapy at second line. Median OS after platinum-based 2-nd line chemotherapy was significantly longer compared to non- platinum chemotherapy group (median OS was 28.1 months, 95% CI: 23.3–42.0 vs. 16.4 months, 95% CI: 13.1–21.0; HR=0.71, 95% CI, 0.51–0.99; P=0.049). This effect was seen, among patients with PFI of 3–6 months (median OS was, 28.1 months, 95% CI: 23.1–42.0 vs 14.3 months, 95% CI: 10.4–40.5, respectively; HR=0.61, 95%CI, 0.39–0.96; P=0.0336). but not in PFI <3months group (HR=0.88, 95% CI, 0.52 to 1.49, P=0.6342). Conclusion: Our results from real world data based on nationwide population cohort study shows that six-months PFI as an arbitrary threshold for subsequent Pt-based chemotherapy is questionable. Biomarkers of platinum sensitivity are needed to identify potential responders, especially in group of patients with PFI 3–6 months. Disclosure: Nothing to disclose.